Associated factors and hemodynamic characteristics of resistant hypertension in the elderly. Issue 3 (7th February 2023) - Geng, Hui; Chen, Xiahuan; Liang, Wenyi; Liu, Meilin
Abstract: The purpose of this study was to explore the associated factors and hemodynamic characteristics of resistant hypertension (RHTN) in the elderly. A total of 283 patients aged ≥60 years with hypertension were evaluated by the CNAP™ monitor. Among them, 240 patients were non‐RHTN (controlled hypertension with use of three or fewer antihypertensive medications) and 43 patients were RHTN (uncontrolled hypertension despite the concurrent use of ≥3 antihypertensive drugs at optimized doses, including a diuretic, or achieving target blood pressure with the use of ≥4 antihypertensive medications). RHTN was associated with higher body mass index (BMI), longer hypertension duration, and coronary heart disease ( p = .004, p < .001, and p = .042, respectively). The mean number of antihypertensive medications was greater in patients with RHTN ( p < .001). Hemodynamic analysis revealed higher cardiac output in the RHTN group than in the non‐RHTN group, while no difference was observed in systemic vascular resistance. Screening for secondary etiology showed that, among the 43 patients with RHTN, 8 (18.6%) had chronic kidney disease, 8 (18.6%) had obstructive sleep apnea, 4 (9.3%) had primary aldosteronism, 2 (4.7%) had renovascular disease. No significant differences were observed in the cardiac output and systemic vascular resistance values between different causes of RHTN. These findings suggest that higher body mass index, longer hypertension duration, and coronary heart disease emerged as the associated factors of RHTN in the elderly. RHTN is characterized by higher cardiac output. Screening for the possible secondary etiology of RHTN in the elderly patients is necessary and important.